Opioid receptor pharmacology and pain - Puig, Margarita (Henry Stewart Talks, 2009)
Opioid receptors: relevance, Opioids in pain management, Opioid analgesics: pharmacology, The endogenous opioid system, Endogenous opioid peptides, Effector systems, Opioid receptor activation, Opioid receptor mediated effects, Opioid receptor polymorphisms, Dimerization, Internalization, Endogenous opioids and opioid receptors are located at peripheral, spinal and supraspinal sites, Opioid analgesia, Cell transfection with a viral vector, Viral vectors expressing endogenous opioid precursors, Drugs that activate opioid receptors, Opioid administration, Paradoxical pain and tolerance, Opioid-induced hyperalgesia: paradoxical pain, Tolerance, Peripheral opioid antagonists, Clinical use of opioids, Opioids in pain management, Principle for safe and effective opioid use